2020
DOI: 10.1111/dme.14271
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment of young offspring in the context of parental type 1 and type 2 diabetes: a systematic review

Abstract: What's new?• Although diabetes like other serious medical conditions impacts family members, with young offspring being particularly vulnerable, this review identified only 10 studies which met inclusion criteria that examined the adjustment of youth to parental type 1 and type 2 diabetes.• This is the first systematic review of research on the psychosocial outcomes in youth of parents with type 1 and type 2 diabetes. It identified research gaps and methodological issues to be addressed by future studies in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Furthermore, given the ongoing increase in numbers of adults living with a serious medical condition worldwide, the number of youth affected by parental illness is likely to steadily rise [ 3 , 4 ]. Parental illness is associated with a significantly higher risk for youth mental and physical health problems, poorer health-related quality of life (HRQoL), and social, educational and employment difficulties that persist well into adulthood [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, having a parent with a chronic illness is related to a significantly higher risk for internalizing problems (e.g., depressive, anxiety, and somatic symptoms), externalizing problems (e.g., aggressive and delinquent behaviors), lower life satisfaction, and loneliness [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given the ongoing increase in numbers of adults living with a serious medical condition worldwide, the number of youth affected by parental illness is likely to steadily rise [ 3 , 4 ]. Parental illness is associated with a significantly higher risk for youth mental and physical health problems, poorer health-related quality of life (HRQoL), and social, educational and employment difficulties that persist well into adulthood [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, having a parent with a chronic illness is related to a significantly higher risk for internalizing problems (e.g., depressive, anxiety, and somatic symptoms), externalizing problems (e.g., aggressive and delinquent behaviors), lower life satisfaction, and loneliness [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic illness in parents may result in psychological distress in offspring, including greater anxiety and depressive symptoms from an increase in daily hassles/responsibilities put on the child and perceived stress of parent's illness 54 . However, data regarding offspring's well‐being specifically surrounding parental T2D are limited and heterogeneous 55 …”
Section: Discussionmentioning
confidence: 99%
“…Adolescents whose parents are chronically ill are significantly more likely to show internalizing problems (i.e., anxious, depressed, and withdrawn behaviors and somatic complaints) than other children (5,8,(14)(15)(16)(17)(18). While in the general population, adolescent females show more internalizing symptoms than males (19)(20)(21), a meta-analysis found that sex differences regarding internalizing problems in children with parental chronic illnesses are negligible (5).…”
Section: Introductionmentioning
confidence: 98%
“…While in the general population, adolescent females show more internalizing symptoms than males (19)(20)(21), a meta-analysis found that sex differences regarding internalizing problems in children with parental chronic illnesses are negligible (5). Knowledge of the longitudinal effects of parental chronic illness is scarce and inconsistent; however, some studies have indicated that the increased risk of internalizing symptoms persists into adulthood (14,22). Hence, research into potential mediating and moderating factors in the pathways between parental chronic illness and internalizing symptoms in adolescents as they transition into adulthood is essential for developing effective interventions for families experiencing parental illness (12,18,23).…”
Section: Introductionmentioning
confidence: 99%